Treatment of Benign Prostatic Hyperplasia: Modern Alternative to Transurethral Resection of the Prostate - Chughtai, Bilal; Te, Alexis E.; Kaplan, Steven A. (Springer New York : Imprint: Springer, 2015)
Treatment of Benign Prostatic Hyperplasia: Modern Techniques is an up-to-date review of modern techniques used to treat benign prostatic hyperplasia. It provides a comprehensive review of both office and operating room based techniques. Both electrosurgical and laser based techniques are covered.These include high powered 532 nm laser photoselective laser vaporization of the prostate (PVP), holmium laser enucleation/ablation of the prostate (HoLEP/HoLAP), and Bipolar Electrovaporization of the Prostate (Bipolar EVP/Bipolar TURP). In addition, a comprehensive review of office based techniques and future therapies currently being developed is presented. Each of these techniques are presented in a balanced fashion with a focus on modern literature.   Treatment of Benign Prostatic Hyperplasia: Modern Techniques will be of great value to Urologists, Urology Residents, Iternists, and Family Practitioners.